Multiuser Based Inventory Information System In Kopel Dolog Semarang - Judia Septiana; Didik Sofian Haryadi; Andik Prakasa Hadi (Lembaga Pengembangan Kinerja Dosen, 2023)
Inventory of goods or inventory is goods or work equipment used in processing the business being carried out or operational equipment of a company. Without inventory, business activities will not be carried out well, for this reason the existence of inventory is very important. The Goods Inventory Information System in a cooperative has quite an important role. One of the problems that often arises in an inventory system is not being able to know the exact number and condition of goods available. In terms of presenting information, the inventory system is implemented on a multiuser basis, where a multiuser system is a computer system that can execute several applications owned by two or more users concurrently and independently. Concurrent means applications can be active simultaneously and compete with each other to use resources such as CPU, memory, hard disk, and so on. Independent means that each application can carry out its tasks without having to care about what other users are running This information system makes it easy to provide inventory information. Apart from that, this system also makes it easier and faster to access information, data and its processing. The new system aims to make it easier for a company to carry out its operational activities, where this system will always ensure that data or information is provided to users quickly, precisely, accurately and at any time it is needed. From the system that has been implemented previously with matters relating to system weaknesses in the company, information or data about the inventory system which was initially very slow to access has now become easier. So that the company's operational activities run smoothly and all weaknesses in the old system can be replaced automatically.